PERTUKARAN DAN HUBUNGAN SOSIAL DI KALANGAN INA-INA (Studi Antropologi Ekonomi dalam Perspektif Strukturalisme) - Rismawati, Rismawati (Academica, 2009)
This research proposed discussion on Ina-Ina economical attempts in Government Market, Manonda, Palu, by focusing on imbedded exchange models of Ina-Ina realm. In addition, present research reveals the continually existence mutual relation in their realm. Ina-Ina behaviors express social relation models in Kaili cultures context. This study proposed to understand Kaili communityâs cultural values which relate to economical development efforts.The result finding revealed that exchange relations which form in mutual relationship in Ina-Ina realm is occur in generalized exchanged, net generalized exchange which individual focused. Farmer in this mutual relation is appear as producer of trading goods for consumer, still, in trading process the farmer requires Ina-Ina to sell directly to consumer.The pattern of mutual relation among them has privately particular relation. These particular relationships, especially in Ina-Ina realm, is maintained and processed through Ina-Ina kinship, neighborhood, religion and friendship. These particular relationships are âhistorically bondâ which produced trust as various moral resources for numerous parties which included in these relations.Hence, it can be concluded that exchange relation that appear in Ina-Ina for their economical effort is horizontal. Within these relations it cannot be found patron-client relation.